Síntese e caracterização de nanoilhas de PZT e BaTiO3 - Albarici, Viviane Cristina (2007)
This work presents a systematic study of synthesis and characterization of ferroelectric nanoislands. Generally three methods were had been studied: polymerized complex method (MPC), hydrothermal synthesis and nonaqueous synthesis. In order to optimize the formation of nanoislands we realized studies about influence of some experimental parameters. When we used MPC the concentration of metallic cátions (Pb2+, Zr4+ and Ti4+) in the polymeric resin, influence of the type calcination (using microwave and conventional oven), the citric acid - metallic cátion ratio (AC:Metal) and the resins deposition method were varied. The results showed that using the spin-coating deposition onto Si (100) substrate, the dilution of the polymeric resin proportionate samples with of distinct particle concentrations. Some of these regions with nanoislands. With the increase of ratio AC: Metal we had the formation of continuous films. The samples prepared by immersion method showed that it is possible the formation of nanoislands with uniform size and distribution by MPC. Tests in MgO and STO substrates were also accomplished based on the optimization discussed above. Tests with one layer indicated only the presence of PZT tetragonal phase. Moreover the optimized immersion conditions lead the formation of a continuous film along the MgO substrate. The sample obtained onto STO substrate presented agglomerated regions. Also hydrothermal synthesis was used to produce PZT nanoparticles. However, even with the variation of the synthesis conditions PZT powders were obtained in a micrometric scale. On the other hand, the nonaqueous route produced a low cristallinity PZT precursor, with was crystallized at lower temperatures than those reported in the literature. Besides, BaTiO3 was also studied. In this case the samples were deposited by immersion and spin-coating. The samples obtained by immersion did not present the formation of nanoislands but regions with agglomerated particles. The viscosity and concentration of organic material were investigated accomplished aiming the formation of films with the thinnest thickness possible to the samples obtained by spin-coating. The formation of continuous films was verified and in some of them the formation of pores was observed. The formation of micrometric islands was observed at higher temperatures.